Efficiency in research, collaboration, and innovation: Parametric and nonparametric approaches in Italian universities - Angela Rella; Anna Rita Dipierro (Journal of Innovation & Knowledge (JIK), 2025)
Over the years, technological advancements and digital transformation have brought significant changes to the Italian education sector. University performance measurement, particularly in terms of efficiency, has been widely debated, given universities' critical role in driving innovation and discovery. This study aims to compare nonparametric and parametric approaches to estimate the efficiency of Italian universities, with a focus on research, collaboration, and innovation. Specifically, data envelopment analysis and stochastic frontier analysis were applied using three different input-output combinations to evaluate the efficiency of 62 Italian public universities in 2021. The findings are valuable from both theoretical and practical perspectives. By identifying best practices and offering targeted insights into areas for performance improvement, this study contributes to the ongoing development of Italian universities and their global competitiveness in research, cooperation, and innovation.
Keywords: I20; 650; University; Data envelopment analysis; Stochastic frontier analysis; Italian context